If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(3x + 5) + -4(3x + 4) + 3(3x + 2) + 8 = 0 Reorder the terms: 3x + 2(5 + 3x) + -4(3x + 4) + 3(3x + 2) + 8 = 0 3x + (5 * 2 + 3x * 2) + -4(3x + 4) + 3(3x + 2) + 8 = 0 3x + (10 + 6x) + -4(3x + 4) + 3(3x + 2) + 8 = 0 Reorder the terms: 3x + 10 + 6x + -4(4 + 3x) + 3(3x + 2) + 8 = 0 3x + 10 + 6x + (4 * -4 + 3x * -4) + 3(3x + 2) + 8 = 0 3x + 10 + 6x + (-16 + -12x) + 3(3x + 2) + 8 = 0 Reorder the terms: 3x + 10 + 6x + -16 + -12x + 3(2 + 3x) + 8 = 0 3x + 10 + 6x + -16 + -12x + (2 * 3 + 3x * 3) + 8 = 0 3x + 10 + 6x + -16 + -12x + (6 + 9x) + 8 = 0 Reorder the terms: 10 + -16 + 6 + 8 + 3x + 6x + -12x + 9x = 0 Combine like terms: 10 + -16 = -6 -6 + 6 + 8 + 3x + 6x + -12x + 9x = 0 Combine like terms: -6 + 6 = 0 0 + 8 + 3x + 6x + -12x + 9x = 0 8 + 3x + 6x + -12x + 9x = 0 Combine like terms: 3x + 6x = 9x 8 + 9x + -12x + 9x = 0 Combine like terms: 9x + -12x = -3x 8 + -3x + 9x = 0 Combine like terms: -3x + 9x = 6x 8 + 6x = 0 Solving 8 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 6x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 6x = 0 + -8 6x = 0 + -8 Combine like terms: 0 + -8 = -8 6x = -8 Divide each side by '6'. x = -1.333333333 Simplifying x = -1.333333333
| (8x+8)+(-9x+9)= | | x^2+8y+6x=y^2-18 | | 3(x+4)=-2(3x-14) | | 4/7x2=13 | | 6x+2=46+2x | | 4/7*2=13 | | 22x-7=180 | | 5-2(x-7)=17-2x | | -3.2b+6=-5.1 | | 4(3x-1)=45 | | 2x^2+7=8x | | -5-2x+x=3 | | -2500-4.05=3000 | | -5(x+12)-13-=-24 | | 4.3b+5=8.1 | | 8.5x^3=79.687x+165.9891 | | 2x^2+7x-2=-2x^2+2x | | x^2+m+7=0 | | 7(x+2)+2=8 | | 5/7n-1=11 | | f(x)=x^5-3x^3+12x | | 3x+3-x=19 | | y+5=12*10 | | (9x+5)=(6x+5) | | 0.2a/4-10=2 | | -3(x-4)-15=-12 | | 2x-3=-7x+105 | | 50+3x^2=2 | | 30/20x=11/20 | | Y-6/y-2 | | f(t)=-16t^2+96t+3 | | a/6+2=4 |